Association study of SLC22A12 rs475688 polymorphism with gout in a Vietnamese population - Tran, Ngan Tra; Tran, Huu Dinh; Le, Thi Thanh Huong; Nguyen, Thuy Duong (Vietnam Journal of Biotechnology, 2025)
Gout is a common inflammatory arthritis caused by the deposition of monosodium urate crystals. Several studies have reported that genetic variants in SLC22A12 were associated with gout susceptibility. However, the obtained results vary indifferent populations. This study aimed to assess the relationship between SLC22A12 rs475688 and gout in a Vietnamese population. Genomic DNA was extracted from peripheral blood samples of 470 participants, including 157 gout patients and 313 healthy controls. Genotyping of SLC22A12 rs475688 was conducted using the PCR-RFLP method. Statistical analysis revealed that the genotype distribution of rs475688 followed Hardy-Weinberg Equilibrium (p>0.05). The C and T allele frequencies were 0.659 and 0.341, respectively. However, there was no significant association between rs475688 and gout in four models (additive, dominant, recessive, and allele (p>0.05). This study provides additional insights into the association between single-nucleotide polymorphisms (SNPs) and gout in the Vietnamese population.